2020
DOI: 10.3390/ijms21207537
|View full text |Cite
|
Sign up to set email alerts
|

Sphingosine-1-Phosphate Receptor Modulators and Oligodendroglial Cells: Beyond Immunomodulation

Abstract: Multiple sclerosis (MS) is an autoimmune inflammatory disease characterized by demyelination, axonal loss, and synaptic impairment in the central nervous system (CNS). The available therapies aim to reduce the severity of the pathology during the early inflammatory stages, but they are not effective in the chronic stage of the disease. In this phase, failure in endogenous remyelination is associated with the impairment of oligodendrocytes progenitor cells (OPCs) to migrate and differentiate into mature myelina… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
22
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 28 publications
(27 citation statements)
references
References 160 publications
0
22
0
Order By: Relevance
“…The affinity of fingolimod-P for the S1P receptor1 (S1PR1) is high ( Brinkmann et al, 2002 ), which is the first identified and the most studied S1P receptor ( Roggeri et al, 2020 ). It is the only S1PR that couples exclusively to Gαi/o ( Lee et al, 1998 ).…”
Section: Mechanisms Of Actionmentioning
confidence: 99%
“…The affinity of fingolimod-P for the S1P receptor1 (S1PR1) is high ( Brinkmann et al, 2002 ), which is the first identified and the most studied S1P receptor ( Roggeri et al, 2020 ). It is the only S1PR that couples exclusively to Gαi/o ( Lee et al, 1998 ).…”
Section: Mechanisms Of Actionmentioning
confidence: 99%
“…Myelination by oligodendrocytes is an ongoing process between infancy and adulthood, and abnormal neural tracts result from abnormalities of the myelinating oligodendrocytes. A pool of undifferentiated oligodendrocyte precursor cells (OPC) remains in the parenchyma of the adult CNS, and they can differentiate into pre-myelinating and myelinating, mature oligodendrocytes [ 1 ]. Abnormal forms are detectable in SCZ: Vikhreva et al reported that 21 patients with SCX had degenerative changes in oligodendrocytes that included swelling, vacuolation, paucity of ribosomes, reduction in volume and number of mitochondria, and an increase in lipofuscin granules [ 2 ].…”
Section: Introduction: General Overview Abnormal Oligodendrocytes In ...mentioning
confidence: 99%
“…As cause for such dysregulated gene expression in OLGs, recent evidence points to the actions of extrinsic factors rather than intrinsic OLG defects (Golan et al, 2021; Kirby et al, 2019; Mozafari et al, 2020; Saraswat et al, 2021; Starost et al, 2020). Thus, targeting druggable signaling pathways with the capacity to modulate gene expression profiles associated with OLG maturation has emerged as a promising approach toward promoting repair of the myelin sheath in MS (Angelini et al, 2021; Gaesser & Fyffe‐Maricich, 2016; Göttle et al, 2019; Green et al, 2017; Jeffries et al, 2016, 2021; Lecca et al, 2020; Mausner‐Fainberg et al, 2021; Mierzwa et al, 2013; Petersen et al, 2021; Rajendran et al, 2021; Roggeri et al, 2020; Skinner & Lane, 2020; Thümmler et al, 2019; Wang et al, 2020; Welliver et al, 2018). Despite an increasing number of potential pathways with promyelinating characteristics, however, clinical translation has, up until now, been below expectation (Abu‐Rub & Miller, 2018; Lubetzki et al, 2020).…”
Section: Discussionmentioning
confidence: 99%